Immigration and clandestinity - Padovese, Valeska (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Migration patterns have changed during the last decades; in the past Italy, was characterized by mass emigration. Now Italy is taking over from Germany the role of Europe's main recipient of immigrants. Till 2001, the officially registered foreign population in Italy stood at 1.362.630. However, clandestine migrants pushed the real figure above 1.600.000. The analyses of residence permit data show that the immigrants are coming increasingly from East European countries, and that they are predominantly concentrated in the North of Italy. The new migratory flows from less developed countries imply many problems to the health assistance. "First aid centres" and "STD centres" offer the early assistance to the immigrants. The main problems are often the language and the immigrants' compliance; it is difficult for them to follow the therapeutic prescriptions, sometimes due to economic reasons only. As the consequence the relations between physicians and patients are not always satisfactory. One important characteristic that distinguishes contemporary immigration from the previous one is the significant presence of undocumented,or illegal, persons. The scarcity of sound information on undocumented immigrants makes the formulation and the implementation of an efficient policy, concerning this clandestine segment of the population, extremely difficult. We present the experience of STD centre of Trieste regarding these problems.
Keywords: Begunci; Emigration And Immigration; Italija; Italy; Preseljevanje; Refugees; Sexually Transmitted Diseases; Spolno prenosljive bolezni